National Schism and Civil Integration : Mutual Relations between the Israeli Central Government & the Israeli Arab Palestinian Minority. - Bligh, Alexander, 1949- (Sussex Academic Press, 2018)
This book analyzes the changes that have taken place in the mutual relationship between the Israeli establishment and the Arab minority since the early 1990s. Changing internal political circumstances on both sides, often led by external world events, have shaped action/reaction and made relations complex. To date this relationship has not been subject to social science analysis, despite some excellent books and journal articles setting out the historic and political relations from 1948 onward, some with a particular emphasis on the Arab polity. National Schism and Civil Integration is the first comprehensive book to tackle the multi-faceted political dimensions of the relationship, and likewise the first to study the linkage between the inner politics of the Arab communities and their relations with the central government. Special attention is paid to the central government's engagement from a security-based dialogue to one encompassing civil policy. The study assesses the emergence of Arab Israeli Palestinian composite nationalism, and the advent of new political groupings, in terms of the political players and how they have been influenced by a growing civil awareness of a more structured and dynamic Palestinian national personality. The study is based on primary sources in all pertinent languages. Resources include official governmental documents, minutes of parliamentary meetings and verdicts of the Supreme Court, as well as Arab manifestos of political parties, declarations and interviews with Arab leaders (MK members, and heads of local councils) and press reports.